Medical and social factors of the possibility of spreading coronavirus infection among fertile aged women - V.V. Podolskyi; Y.H. Antypkin; Vl.V. Podolskyi; T.R. Umanets; T.M. Kaminska; L.A. Livshits; S.A. Rudenko (Publishing House TRILIST, 2021)
Research objective: to determine the risk factors for the spread of coronavirus infection among women of fertile age. Materials and methods. Authors analyzed the medical records (case histories and questionnaires) of 60 women of fertile age who were treated for coronavirus disease. After analysis of medical and social factors women were divided into age groups. Analysis of risk factors for coronavirus disease was determined by calculating the odds ratio according to Wald at p < 0.05. Results. Evaluation of the odds ratio of the COVID-19 chances depending on the nature of work of women of different ages showed that with intense work the risk of disease increases 2.5 times in the age group up to 30 years, which also confirms the analysis of previous indicators, that younger women with moderate workloads have more opportunities to attend mass events and crowds. In the structure of extragenital diseases in women with coronavirus disease, the chances of disease increased 2.6 times in those women who had a history of chronic tonsillitis. Among the history of infectious diseases, the chance ratio of coronavirus disease was increased in women over 30 years of age who had pertussis. Such data may indicate a similar mechanism of development of these diseases, because the causative agent of pertussis also penetrates the upper respiratory tract and may be accompanied by neurological symptoms - the appearance of seizures and bronchospasm. Conclusions. The data obtained in this way allow us to separate a narrower cohort of women of fertile age who may develop coronavirus disease. This will further allow developing proposals for a more efficient distribution of vaccines among the female population of Ukraine and reduce the prevalence of coronavirus infection.